INCLUSIVE EDUCATION IMPLEMENTATION AT SDN SUMBERSARI 1 MALANG - Dina Astika Fitriana; Sulthoni Sulthoni (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2016)
This research focus was the implementation of inclusive education at SDN Malang Sumbersari I in terms of: (1) student participant, (2) educators and education personnel, (3) curriculum, (4) classroom management, (5) learning activities, (6) evaluation and reporting system of learning outcomes and (7) the factors supporting and inclusive education in SDN Sumbersari I Malang. Results from this study were: (1) annually SDN Sumbersari I receive children with special needs in maximum of 2 students, (2) the educators receive training on inclusive education from the education department, (3) the curriculum used is curriculum accommodating, (4) the classroom management is based on the needs of children with special needs, (5) the learning process is adapted from the design of Individual Education Program, (6) determining children with special needs with continuous learners, and there are two types of reports on the results of learning, they are numeral and description, ( 7) supporting factor are the concern of parents and government, inhibiting factor are the parents who do not care and the vagueness of government regulation.